A text book of statistical techniques (FYBCom) - Kumbhojkar G.V. (Phadake prakashan, Kolhapur, 2003)
Stats/Maths
ENGLISH
Keywords: A text book of statistical techniques (FYBCom); Stats/Maths; Stats/Maths